Efektifitas Edukasi Terpadu Dalam Meningkatkan Efikasi Diri Pasien Pasca Operasi Total Hip Dan Knee Replacement di Rumah Sakit - Muhajirin Maliga; Elly Lilianty Sjattar; Syahrul Syahrul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: The research aimed in investigate the effectiveness of the integrated education in improving the self-efficacy of the patients post opeation of the replacements of the hip and knee joints. Methods: In the research the search was carried out using the following databases: PubMed, Google Scholar, ProQuest and Science Direct. The next step was a secondary search based on the reference to the primary search results. There were 9articles so that the total inclusion of 16 articlesResults: The research results obtained after the intervention revealed that the participants of the education empowerment group showed significantly higher self-care competence and self-efficacy. Thus after giving an integrated educational intervention, there was an increase in the self-efficacyof the patients.Conclusion: It could be seen that were was an influence of the intervention on the increase of the self-efficacy of the patients after the operations of replacement of the hip and knee joints.